Rural development and African prosperity: learning from the past - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Sub-Saharan Africa gained its independence with great expectations, most of which have not been fulfilled. Some 32 of the 47 countries on the United Nations' list of poorest countries are African and the World Bank has described this as the greatest...